A phase 2a study investigating the effects of ritlecitinib on brainstem auditory evoked potentials and intraepidermal nerve fiber histology in adults with alopecia areata - Samira Anderson; Guido Cavaletti; Linda J. Hood; Michael Polydefkis; David N. Herrmann; Gary Rance; Brett King; Amy J. McMichael; Maryanne M. Senna; Brian S. Kim; Lynne Napatalung; Robert Wolk; et al. (Wiley, 2024)
Abstract Reversible axonal swelling and brainstem auditory evoked potential (BAEP) changes were observed in standard chronic (9‐month) toxicology studies in dogs treated with ritlecitinib, an oral Janus kinase 3/tyrosine kinase expressed in hepatocellular carcinoma family kinase inhibitor, at exposures higher than the approved 50‐mg human dose. To evaluate the clinical relevance of the dog toxicity finding, this phase 2a, double‐blind study assessed BAEP changes and intraepidermal nerve fiber (IENF) histology in adults with alopecia areata treated with ritlecitinib. Patients were randomized to receive oral ritlecitinib 50 mg once daily (QD) with a 4‐week loading dose of 200 mg QD or placebo for 9 months (placebo‐controlled phase); they then entered the active‐therapy extension and received ritlecitinib 50 mg QD (with a 4‐week loading dose of 200 mg in patients switching from placebo). Among the 71 patients, no notable mean differences in change from baseline (CFB) in Waves I-V interwave latency (primary outcome) or Wave V amplitude on BAEP at a stimulus intensity of 80 dB nHL were observed in the ritlecitinib or placebo group at Month 9, with no notable differences in interwave latency or Wave V amplitude between groups. The CFB in mean or median IENF density and in percentage of IENFs with axonal swellings was minimal and similar between groups at Month 9. Ritlecitinib treatment was also not associated with an imbalanced incidence of neurological and audiological adverse events. These results provide evidence that the BAEP and axonal swelling finding in dogs are not clinically relevant in humans.